Distance Perception in the Oculus Quest and Oculus Quest 2 - Kelly, Jonathan W.; Doty, Taylor A.; Ambourn, Morgan; Cherep, Lucia A. (Frontiers in Virtual Reality, 2022)
Distances in virtual environments (VEs) viewed on a head-mounted display (HMD) are typically underperceived relative to the intended distance. This paper presents an experiment comparing perceived egocentric distance in a real environment with that in a matched VE presented in the Oculus Quest and Oculus Quest 2. Participants made verbal judgments and blind walking judgments to an object on the ground. Both the Quest and Quest 2 produced underperception. Verbal judgments in the VE were 82% and 75% of the object distance, in contrast with real world judgments that were 94% of the object distance. Blind walking judgments were 68% and 70% of object distance in the Quest and Quest 2, respectively, compared to 88% in the real world. This project shows that significant underperception of distance persists even in modern HMDs.